Síntese de 1h-pirazóis usando irradiação de ultra-som e de 2-pirrolonas derivadas do ácido levulínico - Pizzuti, Lucas (2008)
This work describes the synthesis of 4,5-dihydropirazoles through a sonochemical methodology, from the reaction of cyclocondensation of 1,3-diaryl-2-propen-1-ones with aminoguanidine hydrochloride and thiosemicarbazide. These reactions were carried out in ethanol in periods of reduced time concerning to the methods described in the literature. Then, it presents the use of methyl 7,7,7-trichloro-4-methoxy-6-oxo-4-heptenoate for the preparation of a series of ten 1-alkyl(aryl)-5-(3,3,3-trichloro-2-oxopropylidene)pyrrolidin-2-ones, like at a Paal-Knorr synthesis. This transformation can occur with or without isolation of intermediates methyl 4-alkyl(aryl)amino-7,7,7-trichloro-6-oxo-4-heptenoates without significant change in the yields. Subsequently, it was studied the synthetic potential of the previously synthesized pyrrolidin-2-ones front to bromination for getting eight new 1-alkyl(aryl)- 4-bromo-5-(3,3,3-trihalo-2-oxopropylidene)pyrrolidin-2-ones. Bromination occurred in a regiospecific way at 4-position with good yields. Finally, 1-alkyl(aryl)-5-(3,3,3- trihalo-2-oxopropylidene)-1H-pyrrol-2(5H)-ones were obtained from the elimination of the HBr, in alkaline medium, of the brominated pyrrolidin-2-ones.